Classical control of underwater supercavitating vehicles via variable splitting method. (3rd October 2019) - Li, Daijin; Liu, Qiuru; Qin, Kan; Huang, Chuang; Luo, Kai; Dang, Jianjun
ABSTRACT: A conic-like self-excited oscillation is observed during the sailing of supercavitating vehicles. The control strategy for conventional underwater vehicles results in the enhanced oscillation or even divergence because of oscillation characteristics from feedback variables. In this paper, a control strategy based on classical control theory is highlighted to suppress the deterioration of oscillation. A kinetics model is established and linearised to conclude the conic-like oscillation characteristics. The controlled motion parameter, consisting of an inertial link and an oscillation link, is split into Direct Current (DC) and Alternating Current (AC) components at the instantaneous velocity centre. A classical control strategy for the DC component is adopted. The key combinatorial variable of the closed-loop control algorithm is obtained, which can weaken the control effect while the concerned control parameter approaches to the expected value. The development of the oscillation motion can be suppressed, and the relatively smooth output is achieved.